2014
DOI: 10.1111/bph.12598
|View full text |Cite
|
Sign up to set email alerts
|

Arylamine N‐acetyltransferases: from drug metabolism and pharmacogenetics to drug discovery

Abstract: Arylamine N-acetyltransferases (NATs) are polymorphic drug-metabolizing enzymes, acetylating arylamine carcinogens and drugs including hydralazine and sulphonamides. The slow NAT phenotype increases susceptibility to hydralazine and isoniazid toxicity and to occupational bladder cancer. The two polymorphic human NAT loci show linkage disequilibrium. All mammalian Nat genes have an intronless open reading frame and non-coding exons. The human gene products NAT1 and NAT2 have distinct substrate specificities: NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 202 publications
2
105
0
Order By: Relevance
“…Of the genes responsible for the metabolism and transport of anticancer drugs using the WES data, we focused on the genes encoding cytochrome P450 isoforms (CYP2A6, CYP2B6, CYP2C9, CYP2C19, CYP2D6) (Bell et al, 2015;Chen and Goldstein, 2009;Crews et al, 2012;Jin et al, 2005;Kim et al, 2004;Kiyotani et al, 2013;Takimoto et al, 2013;Tamaki et al, 2011;Xie et al, 2003), thiopurine methyltransferase (TPMT) (Chouchana et al, 2014), N-acetyltransferase 2 (NAT2) (Sim et al, 2014), UDP glucuronosyl transferase family 1 member A1 (UGT1A1) (Cheng et al, 2014;Sugatani, 2013), catechol-O-methyltransferase (COMT) (Zubieta et al, 2003), ATP-binding cassette subfamily B member 1 (ABCB1) (Bell et al, 2015;Frederiks et al, 2015), and cytidine deaminase (CDA) (Sugiyama et al, 2007(Sugiyama et al, , 2009, in the present study (Table 2) because the variants of these genes were previously described to affect drug response in Japanese populations (Kurose et al, 2012).…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…Of the genes responsible for the metabolism and transport of anticancer drugs using the WES data, we focused on the genes encoding cytochrome P450 isoforms (CYP2A6, CYP2B6, CYP2C9, CYP2C19, CYP2D6) (Bell et al, 2015;Chen and Goldstein, 2009;Crews et al, 2012;Jin et al, 2005;Kim et al, 2004;Kiyotani et al, 2013;Takimoto et al, 2013;Tamaki et al, 2011;Xie et al, 2003), thiopurine methyltransferase (TPMT) (Chouchana et al, 2014), N-acetyltransferase 2 (NAT2) (Sim et al, 2014), UDP glucuronosyl transferase family 1 member A1 (UGT1A1) (Cheng et al, 2014;Sugatani, 2013), catechol-O-methyltransferase (COMT) (Zubieta et al, 2003), ATP-binding cassette subfamily B member 1 (ABCB1) (Bell et al, 2015;Frederiks et al, 2015), and cytidine deaminase (CDA) (Sugiyama et al, 2007(Sugiyama et al, , 2009, in the present study (Table 2) because the variants of these genes were previously described to affect drug response in Japanese populations (Kurose et al, 2012).…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…11 NAT2 genotypes confer their respective acetylation phenotype as slow, intermediate or rapid, resulting in their specific metabolic rate, therapeutic response, and susceptibility to drug toxicity. 12,13 NAT1 is located in almost every tissue examined, 14 whereas NAT2 is mainly expressed in the liver 3 and gut. 15 The irreversible inhibition and inactivation of biotransformation enzymes like NATs by xenobiotics and their metabolites is of toxicological and clinical significance.…”
Section: Introductionmentioning
confidence: 97%
“…2 N-acetyltransferase 2 (NAT2) (EC 2.3.1.5) is an N-acetylation mediated drug-metabolizing polymorphic enzyme, acts on arylamine carcinogens and drugs including hydralazine and sulfonamide. 3 NAT2 contributes significantly in individual's susceptibility for drugs regarding efficacy and side effects. 4 NAT2 also plays a significant role in detoxification, neutralization of potential carcinogens, and altering the susceptibility to cancer majorly through acetylation.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes play an important role in the detoxification and metabolic activation of xenobiotics [4,7,8] as well as in the synthesis of endogenous compounds [9,10]. potential biomarkers as well as potential drugs for cancer treatment [12][13][14][15]. In another therapeutic perspective, studies showed that NAT gene of Mycobacterium tuberculosis (M. tuberculosis) is part of a cluster essential for the survival of the mycobacteria in the environment inside macrophage [10,16,17].…”
Section: Introductionmentioning
confidence: 99%